Enhancing the image University of the Philippines Mindanao institutional radio ad and audio production thesis - Mendoza, Shirley Anne M.
University of the Philippines in Mindanao is one of the seven constituent universities of the University of the Philippines. Given birth during the year 1995 through Republic Act 7889, Up Mindanao is a premier state university that has aimed to set the benchmark for academic excellence in the region. For several years now, UP Mindanao has gradually been making a name for itself. Despite being a young campus, the university has proven to continually aim for higher standards of education through its participation in local and international conferences and competitions, and through its academic publications. However, it is undeniable that the university still in need of a localized promotion. Despite the existence of Public Relation tools for UP Mindanao, a promotion tool that is targeted to the general public is not yet at hand. The production of an institutional radio advertisement for UP Mindanao addresses this need, created with the purpose of increasing public awareness and enhancing UP Mindanao?s image. The researcher has gone through many stages to materialize the product, from data gathering, scriptwriting, background music production, recording, mixing, and finally, rendering. More than just a production, the researcher also views this as a study on how Public Relation tools such as an institutional advertisement can address every organization?s need for promotion and public image development.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao